2002
DOI: 10.1038/nmat700
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation processes in the deformation of nanocrystalline aluminium by molecular-dynamics simulation

Abstract: The mechanical behaviour of nanocrystalline materials (that is, polycrystals with a grain size of less than 100 nm) remains controversial. Although it is commonly accepted that the intrinsic deformation behaviour of these materials arises from the interplay between dislocation and grain-boundary processes, little is known about the specific deformation mechanisms. Here we use large-scale molecular-dynamics simulations to elucidate this intricate interplay during room-temperature plastic deformation of model na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
452
1
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 924 publications
(521 citation statements)
references
References 26 publications
30
452
1
5
Order By: Relevance
“…It is seen that the hardness in the nanoscale range increases with decreasing , and the value of d * increases with increasing . This is in agreement with the results of atomistic simulations of mechanical deformation [20,[38][39][40]. The simulation results suggested that grain boundary atoms as well as the atoms up to 7-10 lattice parameters away from the grain boundary are heavily involved in plastic deformation.…”
Section: Effect Of Effective Grain Boundary Thicknesssupporting
confidence: 89%
See 2 more Smart Citations
“…It is seen that the hardness in the nanoscale range increases with decreasing , and the value of d * increases with increasing . This is in agreement with the results of atomistic simulations of mechanical deformation [20,[38][39][40]. The simulation results suggested that grain boundary atoms as well as the atoms up to 7-10 lattice parameters away from the grain boundary are heavily involved in plastic deformation.…”
Section: Effect Of Effective Grain Boundary Thicknesssupporting
confidence: 89%
“…The traditional dislocation theories may no longer be applicable to the deformation behavior of nanocrystalline materials. Consistent with the recent experimental observations or models mentioned above, atomistic simulations also suggested that dislocations nucleated at grain boundaries (GBs) carry out plastic deformation in the nanocrystalline regime; once nucleated, these dislocations travel across the grains and are eventually absorbed in the opposite grain boundary [38][39][40]. In a very recent investigation on the plastic deformation recovery in nanocrystalline aluminum and gold films, it was reported that the enhancement of recovery rate could be due to the reduction in pinning sites caused by redistributions of grain boundary impurities during annealing [41].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Considering the initial FCC order of Ni nanowire, here we define only three categories of atoms: 'FCC' atoms, having a local FCC order and considered to be inside the nanowires; 'HCP' atoms, having a local HCP order and classified as stacking faults; and 'other' atoms, all the other atoms considered as belonging to surface. The CNA method has already been used successfully to analyse the structural evolution during the deformation and melting process [32][33][34].…”
Section: Simulation Processmentioning
confidence: 99%
“…MD simulations have also been performed to capture the nanoscale plastic deformation of polycrystalline materials. [12][13][14] Focusing on the specific grain boundaries in our previous study, density functional theory calculations have been applied to evaluate the fault energies of the twin and several CSL grain boundaries, and molecular statics (MS) simulations are performed incipient plastic event on the twin and CSL grain boundaries. 15) In the present study, we constructed two-dimensional thin film model and investigated the deformation characteristics of polycrystalline metal using MS simulations.…”
Section: Introductionmentioning
confidence: 99%